Reconciling Spatial and Temporal Patterns of Cenozoic Shortening, Exhumation, and Subsidence in the Southern Bolivian Andes - Perez, Nicholas D.; Anderson, Ryan B.; Horton, Brian K.; Ohlson, Bailey A.; Calle, Amanda Z. (Frontiers in Earth Science, 2021)
The Bolivian Andes are an archetypal convergent margin orogen with a paired fold-thrust belt and foreland basin. Existing chronostratigraphic constraints highlight a discrepancy between unroofing of the Eastern Cordillera and Interandean Zone fold-thrust systems since 40 Ma and the onset of rapid sediment accumulation in the Subandean Chaco foreland after 11 Ma, previously attributed to Miocene climate shifts. New results from magnetostratigraphic, backstripping, erosional volumetric calculations, and flexural modeling efforts are integrated with existing structural and thermochronologic datasets to investigate the linkages between shortening, exhumation, and subsidence. Magnetostratigraphic and backstripping results determine tectonic subsidence in the Chaco foreland basin, which informs flexural models that evaluate topographic load and lithospheric parameters. These models show that Chaco foreland subsidence is consistent with a range of loading scenarios. Eroded volumes from the fold-thrust belt were sufficient to fill the Chaco foreland basin, further supporting the linkage between sediment source and sink. Erosional beveling of the Eastern Cordillera, local intermontane sediment accumulation after 30–25 Ma, and regional development of the high-elevation San Juan del Oro geomorphic surface from 25 to 10 Ma suggest that the western Eastern Cordillera did not store the large sediment volume expected from erosion of the fold-thrust belt, which arrived in the Subandean Zone after 11 Ma. Eocene to middle Miocene foreland basin accumulation was likely focused between the Eastern Cordillera and Interandean Zone, and has been almost completely recycled into the modern Subandean foreland basin. The delay between initial fold-thrust belt exhumation (early Cenozoic) and rapid Subandean subsidence (late Cenozoic) highlights the interplay between protracted shortening, underthrusting, and foreland basin recycling. Only with sufficient crustal shortening, accommodated by eastward advance of the fold-thrust belt and attendant underthrusting of Brazilian Shield lithosphere beneath the Subandes, did the Subandean zone enter proximal foreland basin deposystems after ca. 11 Ma. Prior to the late Miocene, the precursor flexural basin was situated westward and not wide enough to incorporate the distal Subandean Zone. These results highlight the interplay between a range of crustal and surface processes linked to tectonics and Miocene climate shifts on the evolution of the southern Bolivian Andes.